Potensi Pendirian Baitul Mal Wa Tamwil (BMT) di Desa Tolang Julu Kecamatan Sayur Matinggi Kabupaten Tapanuli Selatan - Rindah Febriani Harahap; Budi Gautama Siregar; Rodame Monitorir Napitupulu (Journal of Islamic Social Finance Management, 2020)
AbstractBaitul Mal Wa Tamwil (BMT) has an important meaning for economic development as well as being the core of a community-based economic strength, its presence is needed especially for people who have micro-businesses that can be developed, so with this encouragement researchers are interested in researching the potential for establishing BMTs in Tolang Village. Julu, Sayur Matinggi District, South Tapanuli Regency. The purpose of this study was to determine the potential for establishing BMT in Tolang Julu Village, Sayur Matinggi District, South Tapanuli Regency. This research is a field research with a qualitative approach, is descriptive in nature. The subjects of this research are the people of Tolang Julu Village who have micro-businesses and need funds. The data sources used are primary and secondary data. The results showed that in Tolang Julu Village, Sayur Matinggi District, South Tapanuli Regency, it has the potential to establish BMT. The existing weaknesses and threats can be minimized with a strategy in the SWOT matrix, namely the SO strategy, the WO strategy, the ST strategy, the WT strategy.Keywords: Potential, BMT, SWOT analysis